Method for producing spherical silica powder
By firing in the contact state of spherical silica before the contact state, combined with ultrasonic treatment and thermal treatment, the problem of inconsistent quality of spherical silicon powder in existing technologies and complex processes have been solved. Correctional losses are low -cut spherical silica powder.
Patent Information
- Application Number
- CN202380046385.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-24
AI Technical Summary
The existing spherical silica manufacturing technology is difficult to efficiently produce spherical silica powders with small specific surface area and consistent quality, and the process is complicated and requires effort and cost.
By firing the spherical and pore -shaped and polychigraphy -based silicon preparation in the state of the granules, combined with ultrasonic treatment, drying and thermal treatment, controlling sodium concentration and thermal treatment temperature Made in the manufacturing of sufficient small spherical silica particles.
Efficient manufacturing of spherical silica powder with consistent quality within a narrow range of conditions is achieved, the dielectric loss tangent is reduced, operability is improved, and the mixability and processability of the resin composition are optimized.
Smart Images

Figure BDA0005182017300000281 
Figure BDA0005182017300000311 
Figure BDA0005182017300000331
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing spherical silicon dioxide powder. Background Art
[0002] Silica particles, which are mainly composed of silicon dioxide (SiO2), have been used in various applications, including electronic materials such as printed circuit boards and package wiring substrates, optical materials such as lenses and optical films, functional materials such as catalysts and catalyst carriers, and pigments for coatings and cosmetics.
[0003] The silica used is required to have a small surface area because the silanol groups on the surface may affect other components, increase the viscosity of the slurry, or provide a wet feel.
[0004] In recent years, with the increase in the amount of information communication in the communication field, the use of high-frequency band signals in electronic equipment, communication equipment, etc. has expanded, and materials used in high-frequency band devices are required to have a low dielectric loss tangent. Silicon dioxide has a small dielectric constant (3.9) and a small thermal expansion coefficient (3 to 7.9 ppm / °C). It is promising as a filler material with a low dielectric constant and a low thermal expansion coefficient, and is expected to be used in high-frequency band dielectric devices, etc.
[0005] Silica particles are obtained by, for example, a flame fusion method, a gas phase method, a gas phase oxidation method, a wet method, a sedimentation method, and the like, and various studies have been conducted on the production methods thereof.
[0006] For example, Patent Document 1 proposes a method of dispersing porous silica gel in a high-temperature gas and firing it to make it non-porous, thereby obtaining monodisperse non-porous spherical silica.
[0007] Patent Document 2 describes a method of obtaining synthetic amorphous silica powder by subjecting granulated silica powder to spheroidization, followed by washing and drying.
[0008] Patent Document 3 describes a method of obtaining molten spherical silica by heating and firing porous synthetic silica, pulverizing the pulverized silica, and then thermally melting the pulverized silica.
[0009] Furthermore, Patent Document 4 proposes a method for producing a dielectric loss tangent reduction-treated molten spherical silica powder, which comprises the following dielectric loss tangent reduction treatment: treating a molten spherical silica powder having an average circularity of 0.85 or more and a specific surface area of 1 to 30 m 2 / g of raw material molten spherical silica powder is subjected to a heat treatment at a temperature of 500 to 1100°C for a predetermined time such that heating temperature (°C)×heating time (h) is 1000 to 26400 (°C·h).
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent No. 2921058
[0013] Patent Document 2: Japanese Patent No. 5686099
[0014] Patent Document 3: Japanese Patent Publication No. 4-66809
[0015] Patent Document 4: Japanese Patent No. 6814906 Summary of the invention
[0016] Problem that the invention aims to solve
[0017] In the method described in Patent Document 1, when the processing volume increases, there is a concern that the temperature in the gas becomes uneven, and uniform processing becomes difficult. Therefore, it is not suitable for processing under a narrow range of conditions, and it is difficult to obtain spherical silica powder with consistent quality. In addition, in this method, although particles with a small pore volume are obtained, it is difficult to obtain particles with a low specific surface area. In the method described in Patent Document 1, if you want to further reduce the specific surface area, you need to repeat the same treatment, or you need to further increase the firing temperature. When the firing temperature is excessively increased, the surface of the high-temperature part or the particles with a long residence time melts, and there is a concern that the particles will be firmly welded / sintered to each other. They become coarse particles, which become defects when mixed with resin.
[0018] In the method described in Patent Document 2, fine powder of the silica powder evaporated in argon-oxygen plasma adheres to the surface of the obtained silica powder, and in order to obtain a powder with a low specific surface area, it is necessary to wash and remove the adhered powder.
[0019] Furthermore, in the method described in Patent Document 3, silicon dioxide is melted during the sphericalization of particles, but in order to obtain spherical particles, it is necessary to dropletize the non-spherical silicon dioxide at a high temperature to the extent that it melts, and then cool / solidify the droplets while they are not in contact with each other. In order to precisely control these, large amounts of energy and precise control of the manufacturing process are required, which is not suitable for large-scale production.
[0020] Furthermore, the method described in Patent Document 4 includes a step of preparing molten spherical silica as a raw material, and requires two steps of melting and calcining at high temperatures, which complicates the production process and increases labor and cost.
[0021] An object of one embodiment of the present disclosure is to overcome the above-mentioned problems of the conventional spherical silica production technology and to provide a novel method for producing spherical silica powder that can efficiently produce spherical silica particles having a small specific surface area.
[0022] Another embodiment of the present disclosure aims to solve the problem of overcoming the above-mentioned problems of the existing spherical silica production technology and to provide a novel method for producing spherical silica powder that can efficiently produce spherical silica particles with a sufficiently small dielectric loss tangent and easy to handle.
[0023] A problem to be solved by another embodiment of the present disclosure is to overcome the above-mentioned problems of the conventional spherical silica production technology and to provide a novel method for producing spherical silica powder that can efficiently produce spherical silica particles having a sufficiently small dielectric loss tangent.
[0024] Solutions for solving problems
[0025] The present invention includes aspects related to the following (1) to (14).
[0026] (1) A method for producing spherical silica powder, comprising the step of calcining a spherical and porous silica precursor in a state where particles are in contact with each other.
[0027] (2) A method for producing spherical silica powder according to the above-mentioned (1), wherein, when the above-mentioned silica precursor is subjected to the following ultrasonic treatment, the ratio D2 / D1 of the cumulative 50% particle size D2 based on the volume of the silica precursor after the ultrasonic treatment to the cumulative 50% particle size D1 based on the volume of the silica precursor before the ultrasonic treatment is greater than 0.9.
[0028] Ultrasonic treatment: Distilled water was added to the aforementioned silica precursor to prepare a 0.05 mass % slurry, and ultrasonic dispersion treatment was performed at a frequency of 45 kHz for 2 minutes.
[0029] (3) The method for producing spherical silica powder according to (1) or (2), wherein the silica precursor has a weight reduction rate of 10% or less when dried at 230° C. for 12 hours.
[0030] (4) The method for producing spherical silica powder according to any one of (1) to (3), wherein the silica precursor is calcined by at least one of a heat treatment by standing and a heat treatment by a rotary kiln.
[0031] (5) A method for manufacturing spherical silica powder, which includes a step of heat-treating a spherical and porous silica precursor, wherein the sodium concentration of the silica precursor is 1 to 300 mass ppm. When the sodium concentration is set as x (mass ppm) and the heat-treatment temperature is set as y (°C), the silica precursor is heat-treated at a temperature satisfying -0.97x + 1180 < y < -0.97x + 1310.
[0032] (6) The method for manufacturing spherical silica powder according to the foregoing (5), wherein the sodium concentration of the silica precursor is 1 to 200 mass ppm.
[0033] (7) The method for manufacturing spherical silica powder according to the foregoing (5) or (6), wherein the silica precursor is fired by at least one heat-treatment selected from the group consisting of heat-treatment based on static standing, heat-treatment based on a rotary kiln, and heat-treatment based on spray combustion.
[0034] (8) The method for manufacturing spherical silica powder according to any one of the foregoing (5) to (7), wherein the silica precursor is fired in a state where the particles are in contact with each other.
[0035] (9) A method for manufacturing spherical silica powder, which includes a step of firing a spherical and porous silica precursor, wherein the silica precursor has a pore volume of 0.1 to 2.0 ml / g and a specific surface area of 200 to 1000 m 2 / g.
[0036] (10) The method for manufacturing spherical silica powder according to the foregoing (9), wherein the silica precursor has an average pore diameter of 1.0 to 50.0 nm.
[0037] (11) The method for manufacturing spherical silica powder according to the foregoing (9) or (10), wherein the average circularity of the silica precursor is 0.90 or more.
[0038] (12) The method for manufacturing spherical silica powder according to any one of the foregoing (9) to (11), wherein the silica precursor is fired in a state where the particles are in contact with each other.
[0039] (13) The method for manufacturing spherical silica powder according to any one of the foregoing (9) to (12), wherein the silica precursor is fired by at least one of heat-treatment based on static standing and heat-treatment based on a rotary kiln.
[0040] (14) The manufacturing method of the spherical silica powder according to any one of the foregoing (1) to (13), wherein, after firing, crushing is further performed so that the average circularity of the particles is not less than 0.90.
[0041] Effects of the Invention
[0042] According to an embodiment of the present disclosure, by firing a spherical and porous silica precursor in a state where its particles are in contact with each other, spherical silica powder with a small specific surface area and constant quality can be efficiently manufactured even with a narrow range of processing conditions.
[0043] According to another embodiment of the present disclosure, when the sodium concentration is set to x (mass ppm) and the heat treatment temperature is set to y (°C), a spherical and porous silica precursor with a sodium concentration of 1 to 300 mass ppm is heat-treated at a temperature satisfying -0.97x + 1180 < y < -0.97x + 1310, thereby spherical silica powder with a sufficiently small dielectric loss tangent and excellent operability can be efficiently manufactured.
[0044] According to still another embodiment of the present disclosure, by firing a spherical and porous silica precursor having a pore volume of 0.1 to 2.0 ml / g and a specific surface area of 200 to 1000 m 2 / g, spherical silica powder with a sufficiently small dielectric loss tangent can be efficiently manufactured.
[0045] The spherical silica powder obtained by the manufacturing method of these embodiments of the present disclosure has an excellent mixing property with a resin and an excellent processability of the resin composition because the particle shape is spherical. In addition, the spherical silica powder obtained by the manufacturing method of these embodiments of the present disclosure can be used as materials represented by fillers for electronic materials and optical materials, and can also be used as materials for coatings and cosmetics. Since the dielectric loss tangent is sufficiently small, it is particularly suitable for applications as electronic materials. Detailed Embodiments
[0046] Hereinafter, the present invention will be described, but the present invention is not limited to the examples in the following description. It should be noted that in this specification, "~" indicating a numerical range means including the values described before and after it as the lower limit value and the upper limit value.
[0047] In this specification, "mass" has the same meaning as "weight".
[0048] (Features of the First Manufacturing Method)
[0049] The first manufacturing method of the spherical silica powder of the present embodiment (hereinafter, also referred to as the present manufacturing method 1) includes the following steps: firing the spherical and porous silica precursor in a state where the particles are in contact with each other. If the silica precursor is fired in a state where its particles are in contact with each other, firing can be carried out with a small volume. Therefore, for example, compared with the case where the silica precursor is dispersed in a gas and fired, the temperature unevenness and time unevenness during firing become smaller. As a result, spherical silica powder with a constant quality can be obtained. In the spray combustion method in which the silica precursor is dispersed in a gas, when the raw material powder is blown into the center of the flame, the temperature of the simultaneously blown gas, the dispersion state of the raw material, the temperature difference generated by the difference in the part passing through the flame, the time difference until passing through the flame, the time until cooling accompanied by the air flow (flow velocity) distribution in the device, all of these lead to fluctuations in the firing conditions. When the temperature is low or the time is short, the porous part with a large surface area remains, and particles with a low specific surface area and a low dielectric loss tangent cannot be obtained. If the temperature is too high, the surface of the particles melts and the particles coalesce with each other, resulting in a phenomenon of forming a surface with fine particles attached to the surface. Similarly to the case of low temperature, particles with a low specific surface area and a small dielectric loss tangent cannot be obtained. By firing the silica precursor in a state where its particles are in contact with each other, the firing conditions in each silica precursor are made uniform, and a constant quality is maintained.
[0050] (Features of the second manufacturing method)
[0051] The second manufacturing method of the spherical silica powder of the present embodiment (hereinafter, also referred to as the present manufacturing method 2) includes the following steps: heat-treating the spherical and porous silica precursor, the sodium (Na) concentration of the silica precursor is 1 to 300 mass ppm. When the sodium concentration is set as x (mass ppm) and the heat-treatment temperature is set as y (°C), the silica precursor is heat-treated at a temperature satisfying -0.97x + 1180 < y < -0.97x + 1310. By carrying out the firing of the silica precursor by heat-treatment at a temperature within the above range, it becomes non-porous and spherical silica with unfused particles, and spherical silica particles with high fluidity, high dispersibility in a slurry, a low specific surface area, and a small dielectric loss tangent are obtained.
[0052] (Features of the third manufacturing method)
[0053] The third manufacturing method of the spherical silica powder of the present embodiment (hereinafter, also referred to as the present manufacturing method 3) includes the following steps: firing the spherical and porous silica precursor, the silica precursor has a pore volume of 0.1 to 2.0 ml / g and 200 to 1000 m 2When the pore volume and specific surface area of the silica precursor are within the above ranges, the specific surface area can be sufficiently reduced by calcination, and sintering is unlikely to occur, thereby obtaining spherical silica particles with a low specific surface area and a small dielectric loss tangent.
[0054] (Silica Precursor)
[0055] The silica precursor used in the present production method 1, the present production method 2, and the present production method 3 is a porous one. The silica precursor being porous means that pores are uniformly distributed in the silica precursor.
[0056] By using porous silica particles as a raw material, it is easier to obtain particles whose shape, particle size distribution, etc. are controlled, compared with particles produced by calcining a pulverized non-porous raw material.
[0057] <Sodium (Na) concentration of silica precursor>
[0058] The porous silica is heated to melt the primary particles of several nm to several 10 nm constituting the internal pore structure, and the specific surface area is reduced, and the pores are gradually filled. It is also known that the melting point decreases if sodium is present. According to the research of the present inventors, it is found that by setting the heat treatment conditions corresponding to the sodium concentration in the porous silica precursor, it is possible to obtain silica particles that prevent the particles from fusing with each other and reduce the dielectric loss tangent.
[0059] In the present manufacturing method 2, the silica precursor used is one having a sodium concentration in the range of 1 to 300 mass ppm. If the sodium concentration of the silica precursor is 1 mass ppm or more, it can be non-porous at a low temperature compared to the case of using a silica precursor with a high purity having a sodium concentration lower than 1 mass ppm. If it is 300 mass ppm or less, silica particles with a low dielectric loss tangent can be obtained. The sodium concentration of the silica precursor is preferably 2 mass ppm or more, more preferably 3 mass ppm or more, and further preferably 10 mass ppm or more. In addition, it is preferably 200 mass ppm or less, more preferably less than 200 mass ppm, further preferably 150 mass ppm or less, particularly preferably 100 mass ppm or less, and most preferably 50 mass ppm or less.
[0060] The sodium content of the silica precursor can be measured by adding perchloric acid and hydrofluoric acid to the silica precursor and applying strong heat to remove silicon as a main component, and then using atomic absorption spectrophotometry.
[0061] <Specific surface area of silica precursor>
[0062] In the present production method 1 and the present production method 2, the specific surface area of the silica precursor is preferably 200 to 1000 m2 In the present production method 3, the silica precursor used has a specific surface area of 200 to 1000 m 2 / g. If the specific surface area is 200m 2 / g or more, the specific surface area after sintering can be reduced while suppressing the sintering of the particles. 2 / g or less, the strength of the silica precursor particles is sufficiently high. In addition, if the specific surface area of the silica precursor is within the above range, even if the particles are heated in a state of contact with each other during sintering, the particles will not be firmly bonded to each other, and spherical particles will be obtained. The specific surface area is more preferably 400m 2 / g or more, more preferably 500m 2 / g or more, particularly preferably 700m 2 / g or more, more preferably 950 m 2 / g or less, more preferably 900m 2 / g or less.
[0063] The specific surface area is determined by a multipoint BET method using a nitrogen adsorption method using a specific surface area / pore distribution measuring apparatus (for example, “BELSORP-miniII” manufactured by Microtrac BEL Corp., “TriStar II” manufactured by Micromeritics, etc.).
[0064] <Pore volume of silica precursor>
[0065] In the present manufacturing method 1 and the present manufacturing method 2, the pore volume of the silica precursor is preferably in the range of 0.1 to 2.0 ml / g. In the present manufacturing method 3, the silica precursor used is one having a pore volume in the range of 0.1 to 2.0 ml / g. If the pore volume is 0.1 ml / g or more, the apparent volume of the particles decreases when the silica is non-porous during sintering, the pores between the particles increase, sintering is not easy to occur, or a powder with weak sintering strength is obtained. If the pore volume is 2.0 ml / g or less, the excessive decrease in bulk density during input before sintering can be suppressed, productivity can be improved, and the silica particles are fully shrunk during sintering, and the specific surface area can be fully reduced. In addition, if the pore volume of the silica precursor is in the aforementioned range, even if the particles are heated in a state where they are in contact with each other during sintering, the particles are not firmly bonded to each other, and spherical particles are obtained. The pore volume is more preferably 0.3 ml / g or more, further preferably 0.6 ml / g or more, particularly preferably 0.7 ml / g or more, and more preferably 1.8 ml / g or less, further preferably 1.5 ml / g or less, particularly preferably 1.2 ml / g or less.
[0066] <Average pore diameter of silica precursor>
[0067] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the average pore size of the silica precursor is preferably 1.0 to 50.0 nm. If the average pore size is 1.0 nm or more, the non-porous can be homogeneously made until the inside of the particles, reducing the dielectric loss tangent without bubbles remaining inside. If the average pore size is 50.0 nm or less, the silica particles can be densified (low specific surface area) by calcination without leaving pores, thereby reducing the dielectric loss tangent. The average pore size is more preferably 2.0 nm or more, further preferably 3.0 nm or more, particularly preferably 4.0 nm or more, and more preferably 40.0 nm or less, further preferably 30.0 nm or less, particularly preferably 20.0 nm or less.
[0068] The pore volume and the average pore size are determined by the BJH method based on the nitrogen adsorption method using a specific surface area / pore distribution measuring apparatus (for example, "BELSORP-miniII" manufactured by Microtrac BELCorp., "TriStar II" manufactured by Micromeritics, etc.).
[0069] <Circularity of silica precursor>
[0070] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the silicon dioxide precursor is spherical, and preferably its average circularity is more than 0.90. If the average circularity is more than 0.90, it is substantially spherical, therefore, the specific surface area of the particles can be reduced, and the convex portion will not be applied due to the vibration of the particles, and the active surface will not be exposed, so the silicon dioxide particles can be made low dielectric. The average circularity is more preferably more than 0.92, particularly preferably more than 0.95, and in addition, the closer to the sphere, the more ideal, therefore, most preferably 1.00.
[0071] The circularity can be obtained as follows: the particles are photographed using a scanning electron microscope (e.g., "JCM-7000" manufactured by JEOL Ltd.), and the area and perimeter of the particles are obtained using image analysis software, such as image analysis software attached to a particle image analysis device (e.g., "Morphologi4" manufactured by Malvern), and the area and perimeter of the particles are substituted into the following formula for calculation. It should be noted that the average circularity of 20 particles is obtained as the average circularity.
[0072] Circularity = circumference of a circle with equal projected area / circumference of a particle
[0073] Circumference of a circle with equal projected area: When observing a particle from directly above, find the area of the particle's shadow projected on the plane below, and calculate the length of the outline of a circle with the same area.
[0074] The circumference of a particle: The length of the outline of the particle's shadow projected on the plane below when the particle is viewed from directly above.
[0075] <Particle size distribution of silica precursor>
[0076] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the volume-based cumulative 50% particle size (D50, hereinafter also referred to as "50% particle size") of the silica precursor is preferably 1 to 500 μm. If the 50% particle size (D50) is 1 μm or more, spherical particles can be formed after calcination to reduce the specific surface area. If it is 500 μm or less, it is easy to use as a filler in a resin that is easy to mold. The 50% particle size (D50) is preferably 1 μm or more, more preferably 1.2 μm or more, and further preferably 1.5 μm or more. In addition, it is more preferably 100 μm or less, further preferably 50 μm or less, particularly preferably 20 μm or less, even more preferably 10 μm or less, and most preferably 5 μm or less.
[0077] The 50% particle size (D50) can be determined using a laser diffraction particle size distribution measuring apparatus (eg, "MT3300EXII" manufactured by Microtrac BEL Corp.), an electrical detection method (Coulter counter method) particle size distribution measuring apparatus (eg, "Multisizer 4e" manufactured by Beckman Coulter Coulter), or the like.
[0078] In the manufacturing method 1, when the silica precursor is subjected to the following ultrasonic treatment, it is preferred that the ratio D2 / D1 of the 50% particle size D2 of the silica precursor after the ultrasonic treatment relative to the 50% particle size D1 of the silica precursor before the ultrasonic treatment is 0.9 or more. Ultrasonic treatment: distilled water is added to the aforementioned silica precursor to prepare a 0.05 mass % slurry, and ultrasonic dispersion treatment is performed at a frequency of 45 kHz for 2 minutes.
[0079] The above ratio D2 / D1 indicates the degree to which particles are strongly aggregated before the calcining step. In the present manufacturing method 1, if the ratio D2 / D1 is 0.9 or more, the aggregation of particles of the silica precursor is not excessively strong, and it becomes difficult to sinter during calcining, so it is preferred. The ratio D2 / D1 is more preferably 0.95 or more, further preferably 0.97 or more, and particularly preferably 0.98 or more. In addition, it is preferred that the 50% particle size (D50) of the silica precursor does not change before and after the ultrasonic treatment, so the upper limit is preferably 1.0.
[0080] <Loss on Drying of Silica Precursor>
[0081] In the present production methods 1, 2 and 3, the weight reduction rate of the silica precursor when dried at 230° C. for 12 hours is preferably 10% or less. If the weight reduction rate is 10% or less, when the silica precursor is calcined in a state where the particles thereof are in contact with each other, sintering of the particles is less likely to occur, and spherical silica powder is easily obtained.
[0082] The weight reduction rate is more preferably 9% or less, further preferably 8% or less, and particularly preferably 6% or less. It is desirable that there is no weight change even after drying at 230° C. for 12 hours, so the lower limit is not particularly limited.
[0083] <Ignition loss of silicon dioxide precursor>
[0084] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, it is desirable that the ignition loss of the silica precursor is 5.0 to 15.0 mass%. The ignition loss is the sum of the attached water attached to the silica precursor and the water generated by the condensation of the silanol groups contained in the silica precursor. The silica precursor has a moderate silanol group, so that the condensation is promoted during firing, and the silanol groups become easy to reduce. If the ignition loss is too much, the yield during firing is reduced and the productivity is deteriorated. Therefore, the ignition loss of the silica precursor is preferably 15.0 mass% or less, more preferably 13.0 mass% or less, and most preferably 12.0 mass% or less. If the ignition loss is too little, the silanol groups become easy to remain during firing. Therefore, the ignition loss of the silica precursor is preferably 5.0 mass% or more, more preferably 6.0 mass% or more, and most preferably 7.0 mass% or more.
[0085] Here, the ignition loss is determined as the mass loss when 1 g of the silica precursor is heat-dried at 850° C. for 0.5 hours in accordance with JIS K0067 (1992).
[0086] <Method for Obtaining Silica Precursor>
[0087] In the present production method 1, the present production method 2 and the present production method 3, the silica precursor may be obtained by production or a commercial product may be used. In addition, the commercial porous silica containing sodium may be washed with an acid to adjust the sodium content.
[0088] Examples of methods for producing a silica precursor include a wet method and a granulation method. A wet method refers to any method of producing porous silica using a liquid raw material or a liquid solvent. A granulation method refers to a method of molding silica particles into a spherical shape using a binder or the like.
[0089] Among these, by using a wet method that can control particle size distribution and produce spherical particles, there is no need to adjust the particle shape by pulverization or the like, and fine particles are not mixed, so that particles with a small specific surface area can be obtained after calcination.
[0090] As wet methods capable of synthesizing spherical particles, for example, spraying method, emulsion / gelation method, etc. can be cited. Spraying method is a method of drying silica sol by spray drying to obtain spherical porous particles. As emulsion / gelation method, for example, dispersed phase containing silica precursor and continuous phase are emulsified, and the obtained emulsion is gelled to obtain spherical silica precursor. As an emulsification method, it is preferred to supply the dispersed phase containing silica precursor to the continuous phase by means of a microporous portion or a porous membrane to prepare an emulsion. Thus, an emulsion with uniform droplet diameter is prepared, and as a result, spherical silica with uniform particle size is obtained. As such an emulsification method, a micro-mixer method and a membrane emulsification method can be used. For example, the micro-mixer method is disclosed in International Publication No. 2013 / 062105.
[0091] The obtained silica precursor has a high water content. If the weight loss rate exceeds 10% when dried at 230°C for 12 hours, it is preferably dried until it becomes 10% or less. Examples of drying methods include spray drying, static drying in a dryer, and ventilation treatment with dry air.
[0092] In addition, when the silica precursors are sintered to form large agglomerates, they may be crushed, but if the sintering is too strong, spherical particles cannot be obtained even if they are crushed, and spherical particles cannot be obtained by the crushing process.
[0093] (Method for producing spherical silicon dioxide powder)
[0094] The manufacturing method 1 comprises the following steps: sintering the above-mentioned silicon dioxide precursor in a state where its particles are in contact with each other. The silicon dioxide precursor is sintered by sintering, the specific surface area is reduced, the amount of silanol groups on the surface is reduced, and the dielectric loss tangent is reduced. The silicon dioxide precursor is sintered in a state where the particles are in contact with each other, so that the particles can be configured in a dense state, and the temperature and time unevenness during sintering can be reduced.
[0095] The present production method 2 includes heat-treating the silica precursor at a temperature satisfying the following formula (1) when the sodium concentration is x (mass ppm) and the heat-treatment temperature is y (° C.).
[0096] -0.97x+1180 <y<-0.97x+1310···(1)
[0097] In formula (1), x is 1≤x≤300.
[0098] When the silica precursor is sintered by heat treatment to densify the silica porous body, the heat treatment is performed at a temperature that satisfies the formula (1), thereby obtaining spherical silica particles with high fluidity and high dispersibility in the slurry.
[0099] From the viewpoint of reducing temperature unevenness during sintering, the heat treatment temperature y in formula (1) is more preferably greater than -0.95x+1180, further preferably greater than -0.905x+1180, and particularly preferably greater than -0.9x+1180. In addition, it is more preferably lower than -0.92x+1300, further preferably lower than -x+1300, and particularly preferably lower than -1.5x+1300.
[0100] In the present production method 2, the sodium concentration x is preferably 200 mass ppm or less, more preferably less than 200 mass ppm, further preferably 100 mass ppm or less, particularly preferably 50 mass ppm or less, and preferably 2 mass ppm or more, more preferably 3 mass ppm or more, further preferably 10 mass ppm or more.
[0101] In the present production method 2, x is 0≤x<200, and the heat treatment temperature y preferably satisfies the following formula (2).
[0102] -0.9x+1180 <y<-1.5x+1300···(2)
[0103] By performing the heat treatment at a temperature satisfying the formula (2), spherical silica particles having a further lower dielectric loss tangent can be obtained.
[0104] The manufacturing method 3 includes the following steps: calcining the silica precursor. The silica precursor is calcined by calcining, the specific surface area is reduced, the amount of silanol groups on the surface is reduced, and the dielectric loss tangent is reduced.
[0105] <Firing method>
[0106] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, as the firing means, there is no particular limitation, and heat treatment based on standing, heat treatment based on a rotary kiln, heat treatment based on spray combustion, etc. can be cited. In the heat treatment based on standing, a static electric furnace, a continuous furnace classified as a roller kiln, a tunnel furnace, etc. can be used. In the heat treatment based on a rotary kiln, a horizontal rotary kiln (rotary kiln), a rotary tubular furnace, etc. can be used. Among these, from the viewpoint of the uniformity of firing, it is preferably fired by a heat treatment based on a continuous furnace or a rotary kiln.
[0107] In the present production method 3, by using the above-mentioned silica precursor, spherical particles can be obtained even when heating is performed in a state where the particles are in contact with each other.
[0108] Among these, from the viewpoint of sintering uniformity, it is preferred that sintering be performed by heat treatment by at least one of heat treatment by standing and heat treatment by a rotary kiln in the present manufacturing method 1 and the present manufacturing method 3. In addition, it is preferred that sintering be performed by heat treatment by standing, heat treatment by a rotary kiln, and heat treatment by spray combustion in the present manufacturing method 2.
[0109] <Firing temperature>
[0110] In the present production method 1, the present production method 2 and the present production method 3, the calcining temperature is preferably 700° C. or higher, more preferably 800° C. or higher, further preferably 900° C. or higher, and particularly preferably 1000° C. or higher. If the temperature is too high, the particles tend to be strongly sintered, and the fineness value in the resin composition increases. Therefore, the calcining temperature is preferably 1600° C. or lower, more preferably 1500° C. or lower, and further preferably 1400° C. or lower. That is, the calcining temperature is preferably in the range of 700 to 1600° C.
[0111] <Firing time>
[0112] In the present production method 1, the present production method 2 and the present production method 3, the firing time may be appropriately adjusted depending on the firing apparatus and firing time to be used, and is preferably 0.5 to 50 hours, more preferably 1 to 10 hours, for example.
[0113] <Firing atmosphere>
[0114] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the atmosphere during firing can be an atmosphere containing oxygen, or can be an atmosphere without oxygen. In the case of spheroidization by a wet method, organic substances such as emulsifiers are mostly used, so that the organic substances remain in the silica precursor in most cases. In the case of firing a silica precursor containing a trace amount of organic substances, the organic substances will be carbonized under the condition of less oxygen, and therefore, become the cause of the rise and coloration of the dielectric loss tangent. Thus, in the case where the silica precursor contains organic substances, it is preferably fired under an atmosphere containing oxygen, more preferably under an atmospheric atmosphere.
[0115] <Broken>
[0116] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the spherical silicon dioxide powder particles are sometimes weakly sintered to each other after sintering, so in this case, it can also be crushed. Crushing is preferably carried out in a manner that the average circularity of the particles is not less than 0.90 to maintain the sphericity and specific surface area so that it does not damage the effect of the present invention. In addition, it is preferred that the specific surface area does not increase due to the crushing process. The specific surface area is greatly increased due to the crushing process, which means that a part of the spherical particles is crushed or fine damage is generated on the surface to produce fine powder. The increase in specific surface area leads to an increase in viscosity when dispersed into the resin and a deterioration of the dielectric loss tangent, so it is not preferred.
[0117] The crushing can be performed using a crushing device such as a cyclone mill or a jet mill, or can be performed using a vibrating screen.
[0118] <Surface treatment>
[0119] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the spherical silica powder obtained by sintering can be surface treated with a silane coupling agent. Through this process, the silanol groups present on the surface of the spherical silica powder react with the silane coupling agent, and the silanol groups on the surface are reduced, and the dielectric loss tangent can be suppressed to be relatively low. In addition, the surface of the particles is hydrophobized, and the affinity to the resin is improved, and therefore, the dispersibility of the resin is improved.
[0120] The surface treatment conditions are not particularly limited, and general surface treatment conditions may be used, and a wet treatment method or a dry treatment method may be used. From the viewpoint of performing a uniform treatment, a wet treatment method is preferred.
[0121] <Silane coupling agent>
[0122] Examples of the silane coupling agent used for the surface treatment include aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, and organic silazane compounds, etc. These can be used alone or in combination of two or more.
[0123] Specific examples of the surface treatment agent include aminopropylmethoxysilane, aminopropyltriethoxysilane, ureidopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, N-2 (aminoethyl) aminopropyltrimethoxysilane and other aminosilane coupling agents, glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, glycidyloxypropylmethyldiethoxysilane, glycidylbutyltrimethoxysilane, (3,4-epoxycyclohexyl)ethyltrimethoxysilane and other epoxysilane coupling agents, mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane and other mercaptosilane coupling agents, methyltrimethoxysilane, vinyltrimethoxysilane, octadecyltrimethoxysilane and other epoxysilane coupling agents. Silane coupling agents such as methoxysilane, phenyltrimethoxysilane, methacryloxypropyltrimethoxysilane, imidazole silane, triazine silane, CF3(CF2)7CH2CH2Si(OCH3)3, CF3(CF2)7CH2CH2SiCl3, CF3(CF2)7CH2CH2Si(CH3)(OCH3)2, CF3(CF2)7CH2CH2Si(CH3)C12, CF3(CF2)5CH2CH2SiCl3, CF3(CF2)5CH2CH2Si(OCH3)3, CF3CH2CH2SiCl3, CF3CH2CH2Si(OCH3)3, C8F 17 SO2N(C3H7)CH2CH2CH2Si(OCH3)3, C7F 15 CONHCH2CH2CH2Si(OCH3)3、C8F 17 CO2CH2CH2CH2Si(OCH3)3、C8F 17 -O-CF(CF3)CF2-O-C3H6SiCl3, C3F7-O-(CF(CF3)CF2-O)2-CF(CF3)CONH-(CH2)3Si(OCH3)3 and other fluorine-containing silane coupling agents, hexamethyldisilazane, hexaphenyldisilazane, trisilazane, cyclotrisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane and other organic silazane compounds, etc.
[0124] <Processing volume>
[0125] The treatment amount of the silane coupling agent is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and further preferably 0.10 parts by mass or more, relative to 100 parts by mass of the spherical silica powder, and is preferably 5 parts by mass or less, and more preferably 2 parts by mass or less. That is, the treatment amount of the silane coupling agent is preferably in the range of 0.01 to 5 parts by mass relative to 100 parts by mass of the spherical silica powder.
[0126] Examples of the method for treating with a silane coupling agent include a dry method of spraying the silane coupling agent onto the spherical silica powder, and a wet method of dispersing the spherical silica powder in a solvent and then adding the silane coupling agent to react.
[0127] It should be noted that the treatment of the surface of the spherical silica powder with a silane coupling agent can be confirmed by detecting a peak generated by a substituent of the silane coupling agent by IR. In addition, the amount of the silane coupling agent attached can be measured by the carbon content.
[0128] The spherical silica powder obtained by the present production method 1, the present production method 2, and the present production method 3 is amorphous solid silica.
[0129] (Physical properties of spherical silica powder)
[0130] <Particle size distribution D50>
[0131] The spherical silica powder obtained by the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3 preferably has a 50% particle size (D50) of 1 μm or more. If the 50% particle size (D50) is 1 μm or more, the dielectric loss tangent can be significantly reduced. In addition, if the 50% particle size (D50) becomes excessively large, the value of the fineness meter becomes large. Therefore, when the resin composition containing the spherical silica powder is made into a film, the minimum thickness of the film becomes thicker, so the 50% particle size (D50) is preferably 500 μm or less. The 50% particle size (D50) is more preferably 1.2 μm or more, particularly preferably 1.5 μm or more, and more preferably 100 μm or less, further preferably 50 μm or less, particularly preferably 20 μm or less, especially preferably 10 μm or less, and most preferably 5 μm or less. That is, the 50% particle size (D50) of the spherical silica powder is preferably in the range of 1 to 500 μm.
[0132] <Maximum particle size Dmax>
[0133] The maximum particle size (Dmax) on a volume basis of the spherical silica powder obtained by the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3 is preferably 150 times or less of the 50% particle size (D50), more preferably 100 times or less, further preferably 50 times or less, and particularly preferably 10 times or less. If the maximum particle size (Dmax) is 150 times or less of the 50% particle size (D50), it is not easy to become a defect during processing of the sheet. In addition, the maximum particle size (Dmax) is preferably 1.2 times or more of the 50% particle size (D50), more preferably 1.5 times or more, and further preferably 2 times or more. That is, the maximum particle size (Dmax) of the spherical silica powder is preferably in the range of 1.2 to 150 times the 50% particle size (D50).
[0134] <Number of coarse particles>
[0135] In the present production method 1, the present production method 2 and the present production method 3, the silica precursors are sometimes sintered by calcining the silica precursor. When the number ratio of particles with a particle size of A μm or more of the silica particles after calcination is greater than the number ratio of particles with a particle size of A μm or more estimated from the particle size distribution of the silica precursor, it means that the particles are firmly sintered to each other, and when dispersed in a resin, they act as agglomerated coarse particles rather than spherical particles, causing an increase in the viscosity of the resin, surface defects, etc.
[0136] In the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, in particular, in the case of spherical silica powder with a 50% particle size (D50) of 5 μm or less, the number ratio of particles of 10 μm or more is preferably in the range of less than 3000 ppm. If the number ratio of particles of 10 μm or more in the spherical silica powder with a 50% particle size (D50) of 5 μm or less is less than 3000 ppm, there is basically no coarse particles, and defects in the sheet after thin filming can be reduced. The number ratio of particles of 10 μm or more is more preferably less than 2000 ppm, further preferably less than 1000 ppm, and particularly preferably less than 500 ppm.
[0137] The 50% particle size (D50) and the maximum particle size (Dmax) can be measured by the above-mentioned electrical detection method (Coulter counter method), and the number ratio of particles can be calculated from the measured particle size distribution.
[0138] <Specific surface area>
[0139] The specific surface area of the spherical silica powder obtained by the present production method 1, the present production method 2, and the present production method 3 is preferably 4.0 m 2 / g or less. If the specific surface area is 4.0m 2 / g or less, the viscosity increase during slurrying can be suppressed, and the dielectric loss tangent can be further reduced. In addition, if the specific surface area is 0.2m 2 / g or more, when the spherical silica powder is contained in the resin composition, the contact points with the resin become sufficient, so the compatibility with the resin becomes good, so it is preferred, and it is substantially difficult to obtain less than 0.2 m 2 The specific surface area is more preferably 3.5 m 2 / g or less, more preferably 3.0m 2 / g or less, particularly preferably 2.0m 2 / g or less. That is, the specific surface area is preferably 0.2 to 4.0 m 2 / g range.
[0140] The specific surface area can be measured in the same manner as above.
[0141] <Product of specific surface area A and 50% particle diameter D50 A×D50>
[0142] The specific surface area is also related to the particle size. Generally, as the particle size decreases, the specific surface area increases. The spherical silica powder obtained by the present production method 1, the present production method 2 and the present production method 3 preferably has a specific surface area A (m 2 The product of the particle size (A) and the 50% particle size (D50) (μm) is 20 μm·m 2 / g or less. If the product A×D50 is 20μm·m 2 / g or less, the viscosity increase during slurrying can be suppressed and the dielectric loss tangent can be reduced compared with particles of the same particle size. The product A×D50 is more preferably 10 μm·m 2 / g or less, more preferably 5 μm·m 2 / g or less. The theoretical value of the product A×D50 is 2.7 μm·m 2 / g [Specific surface area = 6 / (true density of silicon dioxide 2.2 (g / cm 3 )×50% particle size (D50) (μm)) is derived], and in reality, it is impossible to achieve a value below this. That is, the product A×D50 is preferably 2.7 to 20 μm·m 2 / g range.
[0143] <Roundness>
[0144] The average circularity of the spherical silica powder obtained by the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3 is preferably 0.90 or more. If the average circularity is 0.90 or more, it is substantially spherical, and therefore, the specific surface area of the particles can be reduced, and the convex portion will not be applied due to the vibration of the particles, and the active surface will not be exposed, so the silica particles can be made low-dielectric. The average circularity is more preferably 0.92 or more, further preferably 0.93 or more, and particularly preferably 0.95 or more. In addition, the closer to a sphere, the more ideal it is, and therefore, 1.00 is most preferably used.
[0145] The average circularity can be calculated by the same method as described above.
[0146] <Dielectric loss tangent>
[0147] For the spherical silica powder obtained by the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3, the dielectric loss tangent in the powder is preferably 0.0020 or less, more preferably 0.0010 or less, further preferably 0.0008 or less, particularly preferably 0.0007 or less, especially preferably 0.0006 or less, and most preferably 0.0005 or less at a frequency of 1 GHz. In particular, in the determination of the dielectric loss tangent and dielectric constant of the powder, when the frequency is above 10 GHz, the sample space becomes smaller and the measurement accuracy deteriorates. Therefore, the measured value at a frequency of 1 GHz is adopted in the present invention. If the dielectric loss tangent of the spherical silica powder at a frequency of 1 GHz is less than 0.0020, an excellent dielectric loss suppression effect can be obtained, and therefore, a substrate and a sheet with improved high-frequency characteristics can be obtained. The smaller the dielectric loss tangent, the more the transmission loss of the circuit is suppressed, and therefore, the lower limit value is not particularly limited.
[0148] The dielectric loss tangent can be measured by a perturbation resonator method using a dedicated device (for example, "Vector Network Analyzer E5063A" manufactured by KEYCOM Corporation).
[0149] <Viscosity of kneaded product>
[0150] The viscosity of the kneaded product containing the spherical silica powder obtained by the present production method 1, the present production method 2, and the present production method 3 is preferably 5000 mPa·s or less as measured by the following measurement method.
[0151] (Measurement method)
[0152] 6 parts by mass of cooked linseed oil specified in JIS K 5421:2000 and 8 parts by mass of spherical silica powder were mixed and kneaded at 2000 rpm for 3 minutes to obtain a kneaded product. The obtained kneaded product was subjected to a rotational rheometer at a shear rate of 1 s -1 The measurement was performed for 30 seconds, and the viscosity at the time of 30 seconds was obtained.
[0153] The shear rate 1s of the kneaded material determined by the above measurement method -1 If the viscosity is less than 5000mPa·s, the amount of solvent added during the molding / film formation of the resin composition containing the spherical silica powder is reduced, the drying speed can be accelerated, and the productivity can be improved. In addition, if the specific surface area of the particle size of the silica powder becomes larger, the viscosity becomes easy to increase when added to the resin composition, but the specific surface area of the spherical silica powder of the present invention is small, so the viscosity of the resin composition can be suppressed. The viscosity of the kneaded product is more preferably less than 4000mPa·s, and more preferably less than 3500mPa·s.
[0154] Shear rate of the aforementioned kneaded product 1 s -1 The lower the viscosity at this time, the more improved the coatability of the resin composition and the productivity. Therefore, the lower limit is not particularly limited.
[0155] <IR peak intensity>
[0156] The IR peak intensity around 3746 cm−1 derived from the isolated silanol groups on the surface of the spherical silica powder obtained by Production Method 1, Production Method 2, and Production Method 3 of the present invention is preferably 0.1 or less, more preferably 0.08 or less, and still more preferably 0.06 or less. The isolated silanol group means a silanol (Si-OH) group that is not bonded to water or the like adsorbed on the silica particles. The amount of isolated silanol (Si-OH) groups on the surface of the silica particles is obtained by IR measurement. Specifically, the IR spectrum is normalized at 800 cm−1, the baseline is made consistent at 3800 cm−1, and then the relative value of the Si-OH peak intensity around 3746 cm−1 is obtained. If there are many isolated silanol groups on the particle surface, when the components mixed in the resin are used for electronic applications, the dielectric loss tends to increase. However, if the IR peak intensity around 3746 cm−1 derived from the isolated silanol groups on the particle surface is 0.1 or less, the dielectric loss can be reduced. -1 near is preferably 0.1 or less, more preferably 0.08 or less, and still more preferably 0.06 or less. The isolated silanol group refers to a silanol (Si-OH) group that is not bonded to water or the like adsorbed on the silica particles. The amount of isolated silanol (Si-OH) groups on the surface of the silica particles is obtained by IR measurement. Specifically, the IR spectrum is normalized at 800 cm -1 and the baseline is made consistent at 3800 cm -1 after which the relative value of the Si-OH peak intensity near 3746 cm -1 is determined. If there are many isolated silanol groups on the particle surface, when the components mixed in the resin are used for electronic applications, the dielectric loss tends to increase. However, if the IR peak intensity near 3746 cm -1 derived from the isolated silanol groups on the particle surface is 0.1 or less, the dielectric loss can be reduced.
[0157] The maximum IR peak intensity of the bonded silanol groups on the surface of the spherical silica powder obtained by Production Method 1, Production Method 2, and Production Method 3 of the present invention, which is in the range of 3300 to 3700 cm−1, is preferably 0.2 or less, more preferably 0.17 or less, and still more preferably 0.15 or less. The bonded silanol group refers to a silanol (Si-OH) group that is bonded to water adsorbed on the silica particles, a silanol group on the silica surface, or the like. The amount of bonded silanol (Si-OH) groups on the surface of the silica particles is obtained by IR measurement. Specifically, the IR spectrum is normalized at 800 cm−1, the baseline is made consistent at 3800 cm−1, and then the relative value of the bonded Si-OH peak intensity is obtained from the maximum peak in the range of 3300 to 3700 cm−1. If there are many bonded silanol groups on the particle surface, when the components mixed in the resin are used for electronic applications, the dielectric loss tends to increase. However, if the maximum IR peak intensity in the range of 3300 to 3700 cm−1 derived from the bonded silanol groups on the particle surface is 0.2 or less, the dielectric loss can be reduced. -1 is preferably 0.2 or less, more preferably 0.17 or less, and still more preferably 0.15 or less. The bonded silanol group refers to a silanol (Si-OH) group that is bonded to water adsorbed on the silica particles, a silanol group on the silica surface, or the like. The amount of bonded silanol (Si-OH) groups on the surface of the silica particles is obtained by IR measurement. Specifically, the IR spectrum is normalized at 800 cm -1 and the baseline is made consistent at 3800 cm -1 after which the relative value of the bonded Si-OH peak intensity is determined from the maximum peak in the range of 3300 to 3700 cm -1 . If there are many bonded silanol groups on the particle surface, when the components mixed in the resin are used for electronic applications, the dielectric loss tends to increase. However, if the maximum IR peak intensity in the range of 3300 to 3700 cm -1 derived from the bonded silanol groups on the particle surface is 0.2 or less, the dielectric loss can be reduced.
[0158] <Oil absorption>
[0159] The spherical silica powder obtained by this manufacturing method 1, this manufacturing method 2 and this manufacturing method 3 is preferably non-porous particles. If it is porous particles, the oil absorption becomes large, the viscosity in the resin can rise, and the specific surface area increases, the silanol (Si-OH) base amount on the surface of the silica particles increases, and there is a tendency for the dielectric loss tangent to deteriorate. Specifically, the oil absorption is preferably less than 100ml / 100g, more preferably less than 70ml / 100g, most preferably less than 50ml / 100g. The lower limit is not particularly limited, and it is substantially difficult to make the oil absorption be less than 20ml / 100g. That is, the oil absorption is preferably more than 20ml / 100g and is the range below 100ml / 100g.
[0160] <Metal content>
[0161] The spherical silica powder obtained by the present production method 1 and the present production method 3 may contain impurity elements within a range that does not hinder the effects of the present invention. Examples of the impurity elements include Ti, Na, K, Mg, Ca, Al, and Fe.
[0162] The total content of alkali metals and alkaline earth metals in the impurity elements is preferably 2000 mass ppm or less, more preferably 1000 mass ppm or less, and further preferably 200 mass ppm or less.
[0163] The raw material silica precursor contains sodium at a concentration of 1 to 300 mass ppm, and therefore the spherical silica powder obtained by the present production method 2 contains sodium in a range of 1 to 300 mass ppm. The sodium concentration is preferably 2 mass ppm or more, more preferably 3 mass ppm or more, and further preferably 10 mass ppm or more, and is preferably 200 mass ppm or less, more preferably less than 200 mass ppm, further preferably 150 mass ppm or less, particularly preferably 100 mass ppm or less, and most preferably 50 mass ppm or less.
[0164] The spherical silica powder obtained by the present production method 2 may contain impurity elements other than sodium within a range that does not hinder the effects of the present invention. Examples of other impurity elements include K, Mg, Ca, Al, Fe, and Ti.
[0165] The total content of alkali metals and alkaline earth metals in impurity elements other than sodium is preferably 1000 mass ppm or less, more preferably 500 mass ppm or less, and further preferably 200 mass ppm or less.
[0166] (Resin composition and slurry composition)
[0167] <Resin composition>
[0168] The spherical silica powder obtained by the present production method 1, the present production method 2, and the present production method 3 has a small specific surface area and therefore has good dispersibility in various solvents and excellent miscibility with resin compositions.
[0169] The resin composition of the present embodiment contains spherical silica powder and a resin. The content of the spherical silica powder in the resin composition is preferably 5 to 90% by mass, more preferably 10 to 70% by mass.
[0170] As resin, epoxy resin, silicone resin, phenolic resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamide-imide, polyetherimide and other polyamides can be used; Polyesters such as polybutylene terephthalate and polyethylene terephthalate; Polyphenylene sulfide, aromatic polyester, polysulfone, liquid crystal polymer, polyether sulfone, polycarbonate, maleimide modified resin, ABS (acrylonitrile butadiene styrene) resin, AAS (acrylonitrile-acrylate rubber styrene) resin, AES (acrylonitrile ethylene propylene diene rubber-styrene) resin, polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE) in one or more kinds of etc. The dielectric loss tangent in the resin composition also depends on the characteristics of the resin, therefore, it is sufficient to consider these selected resins.
[0171] <Slurry composition>
[0172] The spherical silica powder obtained by the present production method 1, the present production method 2 and the present production method 3 can also be used as a filler for a slurry composition. The slurry composition is a muddy composition in which the spherical silica powder is dispersed in an aqueous or oily medium.
[0173] The slurry composition preferably contains 1 to 50% by mass, more preferably 5 to 40% by mass, of the spherical silica powder.
[0174] Examples of the oil-based medium include acetone, methanol, ethanol, butanol, 2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 2-acetoxy-1-methoxypropane, toluene, xylene, methyl ethyl ketone, N,N-dimethylformamide, methyl isobutyl ketone, N-methylpyrrolidone, n-hexane, cyclohexane, cyclohexanone, and naphtha as a mixture thereof. These may be used alone or as a mixture of two or more thereof.
[0175] The resin composition and the slurry composition may contain any component other than the above-mentioned resin and medium. Examples of the optional component include a dispersing aid, a surfactant, and a filler other than silica.
[0176] <Resin film>
[0177] When making resin film with the resin composition comprising the spherical silica powder obtained by this manufacture method 1, this manufacture method 2 and this manufacture method 3, its dielectric loss tangent is preferably less than 0.012, more preferably less than 0.010, and further preferably less than 0.009 at a frequency of 10GHz. If the dielectric loss tangent of the resin film at a frequency of 10GHz is less than 0.012, the electrical properties are excellent, therefore, it can be expected that the application in electronic equipment, communication equipment, etc. is. The smaller the dielectric loss tangent is, the more the transmission loss of the circuit is suppressed, and therefore, the lower limit is not particularly limited.
[0178] The dielectric loss tangent can be measured using a separate dielectric resonator (SPDR) (for example, manufactured by Agilent Technologies).
[0179] In addition, the average linear expansion coefficient of the resin film is preferably 10 to 50 ppm / °C. When the average linear expansion coefficient is within the above range, it is close to the range of the thermal expansion coefficient of copper foil widely used as a substrate, and therefore the electrical properties are excellent. The average linear expansion coefficient is more preferably 12 ppm / °C or more, and further preferably 15 ppm / °C or more, and more preferably 40 ppm / °C or less, and further preferably 30 ppm / °C or less.
[0180] The average linear expansion coefficient is determined as follows: using a thermomechanical analyzer (e.g., "TMA-60" manufactured by Shimadzu Corporation), the above-mentioned resin film is heated at a load of 5N and a heating rate of 2°C / min, the dimensional change of the sample from 30°C to 150°C is measured, and the average is calculated to determine the average linear expansion coefficient.
[0181] <Applications>
[0182] The spherical silica powder obtained by the present manufacturing method 1, the present manufacturing method 2 and the present manufacturing method 3 can be used as a material for cosmetics, various filling materials, and can be particularly suitable for use as a filling material for a resin composition used in the production of electronic substrates used in electronic devices such as personal computers, notebook personal computers, digital cameras, and communication devices such as smart phones and game consoles. Specifically, the spherical silica powder can also be expected to be used in resin compositions, prepregs, metal foil laminates, printed circuit boards, resin sheets, adhesive layers, adhesive films, solder resists, bump reflow, rewiring insulating layers, chip bonding materials, sealing materials, bottom filling materials, mold bottom filling materials, and stacked inductors due to low dielectric loss tangent, low transmission loss, low moisture absorption, and improved peel strength.
[0183] Example
[0184] Hereinafter, the present invention will be described in detail based on Examples, but the present invention is not limited thereto. In the following description, common components are the same.
[0185] In Test Example 1, Examples 11 to 15 are examples.
[0186] In Test Example 2, Examples 21 to 31 are examples.
[0187] In Test Example 3, Examples 41 to 44 are embodiments, and Example 45 is a comparative example.
[0188] <Method for measuring 50% particle size (D50) and maximum particle size (Dmax) in Test Example 1>
[0189] Distilled water was added to the silica precursor / silicon dioxide powder to prepare a 0.05 mass % slurry, which was then treated with an ultrasonic cleaner at a frequency of 45 kHz for 2 minutes. The particle size in the cumulative 50% (50% particle size, D50) and the maximum particle size (Dmax) converted on a volume basis were calculated using a laser diffraction particle size distribution analyzer (Microtrac BEL Corp., MT3300EXII).
[0190] In addition, in order to indicate the degree of aggregation of the silica precursor, a 0.05 mass% slurry of the silica precursor was dispersed in an ultrasonic cleaning machine at a frequency of 45 kHz for 2 minutes, and the 50% particle size (D50) was calculated by the same method, and the ratio D2 / D1 of the 50% particle size D2 of the silica precursor after the ultrasonic treatment to the 50% particle size D1 of the silica precursor before the ultrasonic treatment was obtained.
[0191] <Method for measuring 50% particle size (D50) and ratio of particles of 10 μm or more in Test Examples 2 and 3>
[0192] Distilled water was added to the silica powder to form a 0.05 mass% slurry, and then the slurry was treated at a frequency of 45 kHz for 2 minutes using an ultrasonic cleaner. The particle size at 50% cumulative volume-based conversion (50% particle size, D50) and the ratio of the number of particles larger than 10 μm were calculated using an electrical detection particle size distribution measuring device (Multisizer4e, manufactured by Beckman Coulter) (settings: pore size 50 μm, effective N number 50,000, current 800 μA, gain 4, stirring speed 15, electrolyte ISOTON).
[0193] <Method for measuring average circularity>
[0194] The particles were photographed using a scanning electron microscope (JCM-7000 manufactured by JEOL Ltd.), and the area and perimeter of the particles were obtained using image analysis software (image analysis software included with the particle image analysis device "Morphologi4" manufactured by Malvern Co.), and the results were substituted into the following formula for calculation. The average circularity of 20 silica particles was obtained as the average circularity.
[0195] Circularity = circumference of a circle with equal projected area / circumference of a particle
[0196] Circumference of a circle with equal projected area: When observing a particle from directly above, find the area of the particle's shadow projected on the plane below, and calculate the length of the outline of a circle with the same area.
[0197] The circumference of a particle: The length of the outline of the particle's shadow projected on the plane below when the particle is viewed from directly above.
[0198] Regarding the judgment of whether or not the particles were spherical, particles with an average circularity of 0.90 or more were evaluated as spherical.
[0199] <Method for evaluating disintegration easiness of silicon dioxide powder>
[0200] The calcined silica powder was disintegrated with fingers, and the disintegration ease was checked according to the following criteria.
[0201] [Evaluation Criteria]
[0202] A: Disintegrates easily into a dry state.
[0203] B: It takes time, but it disintegrates into a dry state.
[0204] C: Does not disintegrate into a dry state.
[0205] <Measurement method of dielectric loss tangent>
[0206] The dielectric loss tangent is measured as follows: using a dedicated device (vector network analyzer E5063A, manufactured by KEYCOM Corporation), the perturbation mode resonator method, the test frequency is 1 GHz, the test temperature is about 24°C, the humidity is about 45%, and the measurement number is 3 times. Specifically, the silica powder and polyethylene (PE) powder (FLO-THENE UF-20S manufactured by Sumitomo Seika Co., Ltd.) are measured in such a way that the filling amount of the silica powder becomes 40% by volume, and mixed in a rotation and revolution mixer manufactured by THINKY CORPORATION (ARE-310, rotation speed 2000 rpm, processing time 3 minutes). The mixed powder obtained by measuring the specified volume is filled into a mold frame of 130 mm square × 0.2 mm thick, and a pressurized sheet is made at 185°C, 10 MPa, and 3 minutes. After the dielectric loss tangent of the obtained pressurized sheet was measured, a sheet prepared under the same conditions using only polyethylene powder was used as a blank, and the dielectric loss tangent of only the powder was converted based on the volume mixing ratio.
[0207] <Method for measuring sodium (Na) content>
[0208] The amount of Na was determined by atomic absorption spectrophotometry. Specifically, 1 g of silica powder was dissolved in an acid containing hydrogen fluoride, heated to dryness, and further dissolved in nitric acid to a constant volume, and then absorbance was measured by atomic absorption spectrophotometry.
[0209] <Methods for measuring specific surface area, pore volume and average pore diameter>
[0210] The silica precursor / silica powder was dried under reduced pressure at 230° C. to completely remove moisture, and the sample was used. The specific surface area of the sample was determined by the multipoint BET method using nitrogen in an automatic specific surface area / pore distribution measuring device "TriStar II" manufactured by Micromeritics, and the pore volume and average pore diameter were determined by the BJH method.
[0211] (Example 1: Preparation of silicon dioxide precursor slurry)
[0212] As the dispersed phase, 30 g of No. 3 sodium silicate (manufactured by AGC SI-TECH CO., LTD., sodium silicate aqueous solution, SiO2 / Na2O (molar ratio) = 3, SiO2 concentration = 24 mass %) was used.
[0213] As a continuous phase, 0.7 mass % of sorbitan monooleate (manufactured by Sanyo Chemical Industry Co., Ltd., Ionet S80) as a surfactant was dissolved in n-decane (manufactured by Tosoh Corporation, HC-250, C 10 H 22 ) and it is 150g.
[0214] While stirring the surfactant-containing n-decane as the continuous phase with a homogenizer (manufactured by Microtec Co., Ltd., Physcotron, Generator shaft NS-30UG / 20P), No. 3 sodium silicate as the dispersed phase was added and emulsified at 13,000 rpm for 5 minutes.
[0215] While stirring the obtained emulsion with a three-in-one motor, carbon dioxide gas was blown into it at a rate of 0.4 L / min for 20 minutes to precipitate silica.
[0216] Then, sulfuric acid was added to the aqueous phase containing silica gel obtained by removing the oil phase while stirring at room temperature until the pH became 2, and then the mixture was stirred in a warm bath at 80° C. for 1 hour to remove the residual decane.
[0217] <Test Example 1>
[0218] (Example 11)
[0219] The slurry after the residual solvent removal obtained in Example 1 was passed through 40 ml / g-SiO2 of desalted water heated to 80°C, filtered and washed to obtain a silica filter cake with a moisture content of 60% by mass. Distilled water was further added to the silica filter cake to form a 5% by mass slurry. The obtained slurry was dried in a spray dryer (micro spray dryer B290 manufactured by BUCHI Co., Ltd., Japan) to obtain a silica precursor. It should be noted that the weight loss rate of the silica precursor obtained at this time when it was dried at 230°C for 12 hours was 6.2%.
[0220] The obtained silica precursor was placed in an alumina crucible and heated for 1 hour in an electric furnace set at 1075° C. After the heating treatment, the silica powder cooled to room temperature was pressed onto a stainless steel sieve with a mesh size of 150 μm using a rubber spatula to pass the particles, thereby obtaining silica powder of Example 1.
[0221] The heat-treated silica powder gradually aggregated, but was easily broken up by lightly pressing a rubber spatula with the hand, and all of it could pass through the sieve.
[0222] (Example 12)
[0223] The same operation as in Example 11 was performed until the slurry obtained in Example 1 after the residual solvent was removed was filtered and washed to obtain a silica filter cake with a moisture content of 60% by mass, and then the obtained silica filter cake was dried at 120°C for 12 hours. After that, the total amount of coarsely aggregated silica was crushed by using a stainless steel sieve with a mesh of 45 μm and a rubber scraper, and the silica precursor was obtained by passing through the sieve. It should be noted that the weight loss rate of the silica precursor obtained at this time when it was dried at 230°C for 12 hours was 2.0%.
[0224] The obtained silica precursor was placed in an alumina crucible and heated in an electric furnace set at 1240° C. for 1 hour. After the heating treatment, it was cooled to room temperature, and the total amount of coarsely aggregated silica was crushed using a stainless steel sieve with a mesh size of 150 μm and a rubber scraper while passing through a sieve to obtain silica powder of Example 12.
[0225] (Example 13)
[0226] The same operation as in Example 12 was carried out except that the shelf drying time was set to 2 hours, the water content of the silica cake was set to 80 mass %, and sieving was not performed, to obtain silica powder of Example 13.
[0227] The weight loss rate of the dried silica precursor when dried at 230° C. for 12 hours was 17.7%. In the crushing treatment after calcination, silica that did not pass through the sieve remained.
[0228] (Example 14)
[0229] The same operation as in Example 13 was carried out except that the dried silica precursor was crushed with a stainless steel sieve with a mesh size of 45 μm and a rubber scraper while passing the sieve, thereby obtaining silica powder of Example 14.
[0230] The weight loss rate of the dried silica precursor when dried for 12 hours at 230° C. was 17.7%. In the crushing treatment after calcination, a small amount of silica that did not pass through the sieve remained.
[0231] (Example 15)
[0232] Distilled water was further added to the silica precursor obtained in Example 13 (weight loss when dried at 230°C for 12 hours: 17.7%) to prepare a 5 mass% slurry, and the obtained slurry was dried in a spray dryer (micro spray dryer B290 manufactured by BUCHI Co., Ltd., Japan). Except for this, the same operations as in Example 13 were performed to obtain the silica powder of Example 15.
[0233] The weight loss rate of the silica precursor after spray drying was 3.5% when it was dried at 230° C. for 12 hours.
[0234] Various measurements were performed on the silica precursors and the calcined silica powders of Examples 11 to 15. The results are shown in Table 1.
[0235] [Table 1]
[0236]
[0237] The spherical silica powders of Examples 11 to 15 all have small specific surface areas and small dielectric loss tangents, and low-dielectric spherical silica powders can be obtained by the method of the present invention.
[0238] <Test Example 2>
[0239] (Example 21)
[0240] For the slurry obtained in Example 1 after the removal of the residual solvent, in order to adjust the amount of sodium (Na), 40 ml / g-SiO2 of acidic desalted water adjusted to pH 1 with sulfuric acid was passed through, filtered and washed, and further filtered and washed with desalted water heated to 80° C. until the pH of the washing liquid became 5 or more. The obtained slurry was dried in a spray dryer (micro spray dryer B290 manufactured by BUCHI Co., Ltd., Japan) to obtain a silica precursor. The sodium concentration of the silica precursor was measured and the result was 12 mass ppm.
[0241] The obtained silica precursor was placed in an alumina crucible and heated in an electric furnace at 1280°C for 1 hour. It should be noted that in order to understand the thermal history during the heating treatment, a Referthermo (a ceramic powder is formed and shrinks with good accuracy according to the thermal history) was installed in the same electric furnace. The indicated temperature of the Referthermo was 1266°C.
[0242] The heat-treated silica powder was cooled to room temperature, and the coarsely aggregated silica was crushed using a stainless steel sieve with a mesh size of 150 μm and a rubber scraper, while the silica under the sieve was recovered to obtain the silica powder of Example 21.
[0243] (Examples 22~24)
[0244] After obtaining the silica precursor by the same operation as in Example 21, except that the heat treatment was performed at the temperature shown in Table 2, the same operation as in Example 21 was performed to obtain silica powders of Examples 22 to 24.
[0245] (Examples 25~27)
[0246] In the filtration washing for adjusting the amount of sodium (Na) in Example 21, instead of acidic demineralized water, 250 ml / g-SiO2 of demineralized water heated to 80°C was passed through, and heat treatment was performed at the temperature shown in Table 2. Other than that, the same operations as in Example 21 were carried out to obtain the silica powders of Examples 25 to 27.
[0247] (Examples 28 - 29)
[0248] In the filtration washing for adjusting the amount of sodium (Na) in Example 21, instead of acidic demineralized water, 40 ml / g-SiO2 of demineralized water heated to 80°C was passed through, and heat treatment was performed at the temperature shown in Table 2. Other than that, the same operations as in Example 21 were carried out to obtain the silica powders of Examples 28 to 29.
[0249] (Examples 30 - 31)
[0250] The slurry after removing the residual solvent prepared in the same manner as in Example 21 was filtered and washed with beverage water heated to 80°C until the pH of the washing liquid became 5 or more, and heat treatment was performed at the temperature shown in Table 2. Other than that, the same operations as in Example 21 were carried out to obtain the silica powders of Examples 30 to 31.
[0251] Various measurements were carried out on the silica precursors and the fired silica powders of Examples 21 to 31. The results are shown in Table 2.
[0252] In addition, when the sodium concentration of the silica precursor is set to x (mass ppm) and the heat treatment temperature is set to y (°C), whether the heat treatment temperature (firing temperature) of the silica precursor satisfies Equation (1): -0.97x + 1180 < y < -0.97x + 1310 (1 ≤ x ≤ 300) and Equation (2): -0.9x + 1180 < y < -1.5x + 1300 (1 ≤ x < 200) is also shown in Table 2.
[0253] [Table 2]
[0254]
[0255] The tangent of the dielectric loss angle of the spherical silica powders of Examples 21 to 31 was 0.0010 or less, and after being made low dielectric, spherical silica particles with a sufficiently small tangent of the dielectric loss angle could be manufactured.
[0256] <Test Example 3>
[0257] (Example 41)
[0258] The silica powder of Example 41 was obtained in the same manner as in Example 11.
[0259] (Example 42)
[0260] To the slurry obtained in Example 1 after the removal of the residual solvent, an aqueous sodium hydroxide solution was further added until the pH reached 9, and the mixture was stirred for 1 hour in a warm bath at 90° C. Except for this, the same operation as in Example 41 was carried out to obtain a silica powder of Example 42.
[0261] (Example 43)
[0262] As the dispersed phase, 30 g of a substance obtained by diluting No. 3 sodium silicate (AGC SI-TECH CO., LTD., sodium silicate aqueous solution, SiO2 / Na2O (molar ratio) = 3, SiO2 concentration = 24 mass %) with water to prepare an aqueous solution with SiO2 concentration = 11 mass %, and further adding 30 mass % of sodium chloride relative to the weight of SiO2. In addition, in order to make the average particle size equal to that of Examples 41 and 42, the rotation speed during stirring and emulsification was set to 10000 rpm, and other than that, the same operation as in Example 41 was performed to obtain the silica powder of Example 43.
[0263] The spherical silica powder obtained had a slightly rough feel after calcination, but was partially loosened during the pretreatment by ultrasonic treatment before the particle size distribution measurement. Therefore, it was disintegrated to a dry state and could be measured without blocking the pores of 50 μm.
[0264] (Example 44)
[0265] In the operation of Example 43, the same aging step as in Example 42 was applied. Except for this, the same operation as in Example 43 was carried out to obtain the silica powder of Example 44.
[0266] (Example 45)
[0267] Commercially available silica gel (manufactured by Kanto Chemical Co., Ltd., silica gel white granules) was pulverized in a mortar and classified to obtain crushed silica having an average particle size of 43 μm, which was used as a silica precursor.
[0268] The same calcination and crushing treatments as in Example 41 were carried out to obtain strongly agglomerated particles that could not all pass through the sieve.
[0269] Various measurements were performed on the silica precursors and the calcined silica powders of Examples 41 to 45. The results are shown in Table 3.
[0270] [Table 3]
[0271]
[0272] According to the results in Table 3, the dielectric loss tangent of the spherical silica powders of Examples 41 to 44 was 0.0020 or less, indicating that the dielectric loss tangent was reduced. On the other hand, the particles of Example 45 were strongly aggregated after calcination and could not be broken, so the dielectric loss tangent could not be measured.
[0273] The present invention is described in detail and with reference to specific embodiments, but it is obvious to those skilled in the art that various changes and modifications may be made without departing from the subject matter and scope of the present invention. This application is based on Japanese patent applications (Japanese Patent Application Nos. 2022-095197, 2022-095198, and 2022-095199) filed on June 13, 2022, the contents of which are incorporated herein by reference.
Claims
1. A method for manufacturing spherical silica powder, which comprises the following steps: firing a spherical and porous silica precursor in a state where the particles are in contact with each other.
2. The method for producing spherical silicon dioxide powder according to claim 1, wherein: When the following ultrasonic treatment is performed on the silica precursor, the ratio D2 / D1 of the cumulative 50% particle size D2 based on volume of the silica precursor after the ultrasonic treatment to the cumulative 50% particle size D1 based on volume of the silica precursor before the ultrasonic treatment is 0.9 or more. Ultrasonic treatment: Distilled water is added to the silica precursor to form a 0.05 mass% slurry, and ultrasonic dispersion treatment is performed at a frequency of 45 kHz for 2 minutes.
3. The method for producing spherical silicon dioxide powder according to claim 1 or 2, wherein: The weight reduction rate of the silica precursor when dried at 230 °C for 12 hours is 10% or less.
4. The method for producing spherical silicon dioxide powder according to any one of claims 1 to 3, wherein The silica precursor is fired by at least one heat treatment selected from heat treatment based on standing and heat treatment based on a rotary kiln.
5. A method for manufacturing spherical silica powder, which comprises a step of heat-treating a spherical and porous silica precursor, wherein the sodium concentration of the silica precursor is 1 to 300 mass ppm. When the sodium concentration is set as x (mass ppm) and the heat treatment temperature is set as y (°C), the silica precursor is heat-treated at a temperature satisfying -0.97x + 1180 < y < -0.97x + 1310.
6. The method for producing spherical silicon dioxide powder according to claim 5, wherein: The sodium concentration of the silica precursor is 1 to 200 mass ppm.
7. The method for producing spherical silicon dioxide powder according to claim 5 or 6, wherein: The silica precursor is fired by at least one heat treatment selected from the group consisting of heat treatment based on standing, heat treatment based on a rotary kiln, and heat treatment based on spray combustion.
8. The method for producing spherical silicon dioxide powder according to any one of claims 5 to 7, wherein The silica precursor is fired in a state where the particles are in contact with each other.
9. A method for producing spherical silica powder, comprising the step of calcining a spherical and porous silica precursor, wherein the silica precursor has a pore volume of 0.1 to 2.0 ml / g and a pore volume of 200 to 1000 m 2 / g specific surface area.
10. The method for producing spherical silicon dioxide powder according to claim 9, wherein: The silica precursor has an average pore diameter of 1.0 to 50.0 nm.
11. The method for producing spherical silicon dioxide powder according to claim 9 or 10, wherein: The average circularity of the silica precursor is 0.90 or more.
12. The method for producing spherical silicon dioxide powder according to any one of claims 9 to 11, wherein The silica precursor is fired in a state where the particles are in contact with each other.
13. The method for producing spherical silicon dioxide powder according to any one of claims 9 to 12, wherein: The silica precursor is fired by at least one heat treatment selected from heat treatment based on standing and heat treatment based on a rotary kiln.
14. The method for producing spherical silicon dioxide powder according to any one of claims 1 to 13, wherein After firing, crushing is further performed with an average circularity of the particles not less than 0.90.
Citation Information
Patent Citations
Limiting device for insufficient excitation
JP1981086099A
Molten spherical silica and its production
JP1992066809B2
Casing unit
JP2022095197A
Information processing apparatus
JP2022095198A
Unauthorized communication prevention system and unauthorized communication prevention method
JP2022095199A